2014
DOI: 10.1177/2325957414555225
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis as a Manifestation of Immune Reconstitution Inflammatory Syndrome (IRIS) in HIV-Infected Patients

Abstract: Introduction After the onset of highly active antiretroviral therapy (HAART), some HIV-infected patients present a severe inflammation in response to a latent or a previously treated opportunistic pathogen termed immune reconstitution inflammatory syndrome (IRIS). Few reports of tegumentary and visceral leishmaniasis have been described in association with IRIS. Methods A systematic literature review of IRIS in association with leishmaniasis identified 34 reported cases. Results and Discussion The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
(106 reference statements)
1
12
0
Order By: Relevance
“…All six cases reported by 2007 followed the unmasking pattern as also observed in our case [10]. The analysis of 34 cases of both visceral and muco-/cutaneous disease associated with IRIS identified a rapid increase of peripheral CD4 + T cell numbers following the initiation of antiretroviral therapy as one risk factor [11].…”
Section: Case Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…All six cases reported by 2007 followed the unmasking pattern as also observed in our case [10]. The analysis of 34 cases of both visceral and muco-/cutaneous disease associated with IRIS identified a rapid increase of peripheral CD4 + T cell numbers following the initiation of antiretroviral therapy as one risk factor [11].…”
Section: Case Discussionsupporting
confidence: 77%
“…VL shortly after initiation of antiretroviral therapy has been reported before in the context of an immune reconstitution inflammatory syndrome (IRIS), which is defined as a hyperreactive immunologic response during the increase of peripheral CD4 + T-cell numbers upon treatment [10,11]. It is also observed in association with mycobacteriosis, cryptococcosis, or infection with JC-virus, Herpes-and Hepatitis-Virus [12].…”
Section: Case Discussionmentioning
confidence: 96%
“…2 HIV-Leishmania co-infection has caused unusual presentations and different treatment responses in India. 13,14,15 Recent study done in Sri Lanka revealed variety of atypical lesions of CL and their clinical profile and treatment outcome. 8 This study was planned tohelp in identifying demographic correlates, common co-existing skin manifestations of CL and their prevalence as well as correlations between severity of primary lesions and other co-existing manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral leishmaniasis–HIV coinfection has a number of unique clinical and immunological features. In contrast to many other HIV-associated opportunistic infections, CD4 + T cell reconstitution is severely delayed (even if virological suppression is reached) and the immune reconstitution inflammatory syndrome to a Leishmania infection after initiation of cART appears relatively rare, indicating a persistent suppression of host immunity ( 33 , 34 ). Atypical clinical presentations can occur and amastigotes have been detected in tissues such as the intestine, where parasites are mostly undetectable in the immunocompetent host ( 14 , 35 ).…”
Section: Introductionmentioning
confidence: 99%